Role Of Telemedicine In Improving Maternal And Neonatal Health In Sub-Saharan Africa - Fowler, Omolayo; Christiana Sonuyi, Onaopemipo (International Journal of Psychosocial Rehabilitation, 2023)
Several barriers have been shown to contribute to the burden and disparities among infant and pregnant women particularly in sub-Saharan African such as lack of access to quality health care services, isolated communities, deficiency of well-equipped facilities and a lack of well-trained health care professionals. These challenges have resulted into chronic diseases, health burden and health challenges among infant and pregnant women such as maternal mortality, morbidity, infection, eclampsia, hemorrhage, mental health conditions, embolism and gestational hypertension. One of the methods that have been proposed to be effective in overcoming, preventing, monitoring, assessing, educating and evaluating these challenges is Telemedicine. This technology is based on information and communication strategies like mHealth, eHealth, education, and telehealth using smartphones, telephone, computer, videoconferencing, digital image technologies, applications, algorithms, medical devices and other wireless and wearable gadgets. Thus, this review is aimed at giving an overview on the role of telemedicine in improving maternal and neonatal health in Sub-Saharan Africa.